A Photo Elicitation Study on Chronically Ill Adolescents' Identity Constructions During Transition. (3rd March 2016) - Hanghøj, Signe; Boisen, Kirsten A.; Schmiegelow, Kjeld; Hølge-Hazelton, Bibi
Adolescence is an important phase of life with increasing independence and identity development, and a vulnerable period of life for chronically ill adolescents with a high occurrence of insufficient treatment adherence. We conducted four photo elicitation focus group interviews with 14 adolescents (12-20 years) with juvenile idiopathic arthritis to investigate identity constructions during transition. Using a discourse analysis approach, six identity types were identified distributed on normal and marginal identities, which were lived either at home (home arena) or outside home with peers (out arena). Most participants positioned themselves as normal in the out arena and as ill in the home arena. Few participants positioned themselves as ill in an out arena, and they described how peers perceived this as a marginal and skewed behavior. This study contributes to a better understanding of why it can be extremely difficult to live with a chronic illness during adolescence.